(untitled) (ELang | An English Language Education Journal, 2018)
The research paper is entitled “The Effectiveness of Cubing Strategy in Teaching Writing Descriptive Text”. There are two aims in this research; those are to find out whether or not the use of cubing strategy is effective to improve students’ ability in writing descriptive text and to know students’ responses towards the use of cubing strategy for improving students’ ability in writing descriptive text. The population of this research was the first grade students of SMAN 2 Majalaya. The number of the sample was 37 students for experimental group and 37 students for control group. The result of the pre-test showed that the t-test value was 0.012, where t-table at p=0.05 with Df=N1+N2-2=37+37-2=72 at the level of significance 0.05 for two tailed was 1.990. Then the writer could observe that the t observe was lower than t-table (0.012 < 1.990). There was no significant difference between experimental and control group at the beginning of the study or before the treatments were given. The result of post-test showed that the t-test value was 4.322, where t-table at p=0.05 with Df=N1+N2-2=37+37-2=72 at p=0.05 of two tailed, the critical value of t was 1.990, so t-observe was higher than that t-table (4.322 > 1.990). It means that there was significant difference in the result between using cubing as a strategy to improve students’ ability in writing descriptive text and conventional method. The questionnaire was only distributed to the experimental group to find out how the students’ responses toward the use of cubing strategy. The result showed that almost all of students (86.49%) liked and agreed with the use of cubing strategy and it helped them to write descriptive text. It meant that almost all of the students gave the positive responses towards the use of cubing strategy. Keywords: Cubing strategy, writing, descriptive text